Stepped 2-Level Operation of Three-Port Modular DC/DC Converter Applied in HVDC Application - Hongcheng You (IEEE Access, 2018)
High-voltage dc/dc converter is the key equipment to interconnect high-voltage dc (HVdc) systems with different voltage levels and to build dc grid. This paper presents a novel three-port modular dc/dc converter (TP-MDCC) to interconnect three HVdc systems, and it offers the following merits: 1) high efficiency for the elimination of multiple dc/ac conversion stages and transformers; 2) modular design and small submodule (SM) capacitance requirement; 3) low dv/dt stress; and 4) the sorting algorithm of the SM capacitor voltages needs only to be executed twice in a period, which poses small computation burden. In this paper, the operation principle and the control strategy of the TP-MDCC are analyzed, and the simulation and experimental results verify the effectiveness of the converter.